Development of Novel 4-Arylpyridin-2-one and 6-Arylpyrimidin-4-one Positive Allosteric Modulators of the M(1) Muscarinic Acetylcholine Receptor - Jörg, Manuela (ChemMedChem, 2021)
This study investigated the structure-activity relationships of 4-phenylpyridin-2-one and 6-phenylpyrimidin-4-one muscarinic M(1) acetylcholine receptor (M(1) mAChRs) positive allosteric modulators (PAMs). The presented series focuses on modifications to the core and top motif of the reported leads, MIPS1650 (1) and MIPS1780 (2). Profiling of our novel analogues showed that these modifications result in more nuanced effects on the allosteric properties compared to our previous compounds with alterations to the biaryl pendant. Further pharmacological characterisation of the selected compounds in radioligand binding, IP(1) accumulation and β-arrestin 2 recruitment assays demonstrated that, despite primarily acting as affinity modulators, the PAMs displayed different pharmacological properties across the two cellular assays. The novel PAM 7f is a potential lead candidate for further development of peripherally restricted M(1) PAMs, due to its lower blood–brain-barrier (BBB) permeability and improved exposure in the periphery compared to lead 2.